To stand tall, to look people in the eye: empowerment of Ethiopian women immigrants via an employment programme. (2nd September 2018) - Sharaby, R.; Lipkin, A.
Abstract: Immigrant women encounter unique adjustment difficulties, which block their inclusion in the labour market. Those who arrive from traditional societies, such as those who are the subject of the present article, must also cope with gaps that originate in cultural differences. This article examines a unique government empowerment programme called the 'Woman of Valour' that was established for women immigrants from Ethiopia. The programme's goal is inclusion and advancement through the employment channel, but it perceives the woman holistically, as part of the family, community and society. The article exposes the many 'baggages' with which the women arrived in Israel. It concludes that they experienced a three-stage empowerment process within the framework of the programme: (1) Going out from the 'domestic sphere' to the 'public sphere'. (2) Learning, where they were exposed to a large amount of information, which according to feminist thinking is perceived as generating change. They learned to 'stand tall' and 'look people in the eye.' These are significant physiological changes that reflect empowerment, according to the ethnic-cultural criteria of the researched women. (3) Internal change, which gradually influenced their conduct in the public sphere.